APPLICATION OF DEEP LEARNING APPROACH IN INDONESIAN LANGUAGE LEARNING AT SMA NEGERI 1 KANDIS 2025/2026 - Fesehi Triani; Muhammad Mukhlis (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the application of the deep learning approach in learning Indonesian at SMA Negeri 1 Kandis which includes aspects of planning, implementation, and obstacles faced. The research uses a descriptive qualitative approach with case study methods and content analysis techniques. Data was collected through in-depth interviews, classroom observations, and study of teaching module documents. The results of the study show that at the planning stage, teachers have been able to develop teaching modules that lead to learning based on higher order thinking skills (HOTS), contextual activities, and active student involvement, with good to excellent quality categories. At the implementation stage, learning has followed a deep learning syntax which includes understanding, applying, and reflecting, as well as showing the characteristics of collaborative, contextual, and participatory learning with an excellent category. However, the aspects of reflection and metacognitive reinforcement are still not optimal because they have not been systematically structured. The obstacles found include time constraints, variations in students' abilities and activities, the use of technology that has not been maximized, and students' learning habits that still tend to be passive. This study concludes that the deep learning approach has the potential to improve the quality of Indonesian language learning, but requires strengthening the aspects of reflection, authentic assessment, and support for teacher facilities and competencies so that the implementation is more optimal.